Research methodology : A Practical and Scientific Approach - Bairagi, Vinayak; Munot, Mousami V. (Boca Raton : CRC Press, Taylor and Francis Group, 2019)
This book offers a design research methodology intended to improve the quality of design research- its academic credibility, industrial significance and societal contribution by enabling more thorough, efficient and effective procedures.
1. Introduction to Research 2. Literature Survey and Problem Statement 3. Research Design 4. Basic Instrumentation 5. Applied Statistics 6. Presenting and Publishing the Research Findings 7. Plagiarism 8. Intellectual Property Rights
Includes bibliographical references and index.
Description based on print version record.
Keywords: Research -- Methodology; REFERENCE / Questions & Answers; MATHEMATICS / Probability & Statistics / General; Research -- Methodology